HIJRAH AND RECTIFICATION OF MUSLIM IDENTITY: The Case of Campus Da’wah Activists in Pontianak City - Syahbudi, Syahbudi; Ardiansyah, Ardiansyah; Ali, Roslan bin; Hayanuddin, Safri (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2024)
From its inception, hijrah in Islamic tradition referred to the Prophet Muhammad’s geographical migration from a perilous environment to a place of peace. Over time, however, hijrah has evolved to encompass broader notions of transformation, including shifts in lifestyle, adoption of Islamic attire, and changes in social relationships. These developments illustrate that hijrah is a fluid and multifaceted concept. It explores how these activists experience and manage hijrah in terms of acceptance and supervision. Key questions addressed include: How do campus da’wah activists construct and sustain their identity through hijrah in the context of modernity? What role does the state play in shaping religious life? The article argues that hijrah represents not only a journey of self-improvement but also a subtle form of resistance to state influence in regulating religious practices, particularly as communities navigate the negative aspects of modernity. The interplay between hijrah, the state, and modernity is characterized by selective engagement, prioritizing lifestyle changes over ideological shifts. Using Peter L. Berger’s social construction framework—encompassing externalization, objectification, and internalization—the article concludes that the spirit of hijrah within this framework significantly shapes perspectives on the state’s role in religious affairs.Keywords: Hijrah; identity, state role, Islamic thought, modernity.